2005
DOI: 10.1177/0895904804270774
|View full text |Cite
|
Sign up to set email alerts
|

Life in the Fast Track: How States Seek to Balance Incentives and Quality in Alternative Teacher Certification Programs

Abstract: The prospect of overseeing the rapid preparation of many participants in fasttrack alternative certification programs presents several challenges for state education officials who seek to maintain, or even enhance, the quality of the state's teaching force. This study examined a range of fast-track alternative teacher certification programs in 11 sites in three states-Connecticut, Louisiana, and Massachusetts. We found that participants were attracted by the incentives of the fast-track programs but also expec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 11 publications
0
35
0
Order By: Relevance
“…A great deal of discussion has been held on the advantages and disadvantages of these programs, which are often shorter in length than the traditional ones, as well as on their impact on the teaching force, on schools, on students and on teaching per se as a profession (Wright 2001). Claims made in favor of these programs include the constraint of teacher shortages (the quantitative claim) and the need to attract high-quality individuals with the appropriate personality and relevant academic background but who would not have come to the teaching field at all, had these programs not been available (the qualitative claim) (Johnson, Birkeland, and Peske 2005). In addition, economic arguments have been raised regarding the need to lower the high cost of traditional teacher training.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…A great deal of discussion has been held on the advantages and disadvantages of these programs, which are often shorter in length than the traditional ones, as well as on their impact on the teaching force, on schools, on students and on teaching per se as a profession (Wright 2001). Claims made in favor of these programs include the constraint of teacher shortages (the quantitative claim) and the need to attract high-quality individuals with the appropriate personality and relevant academic background but who would not have come to the teaching field at all, had these programs not been available (the qualitative claim) (Johnson, Birkeland, and Peske 2005). In addition, economic arguments have been raised regarding the need to lower the high cost of traditional teacher training.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Research has also shown that alternative certification programmes are not only successful in attracting more teachers of colour, but also a higher proportion of males, those teachers willing to work in difficult settings and experienced professionals from other fields, who want to teach but are discouraged by the extensive requirements of a traditional 66 A. Moran programme (Haberman 1999;Ballou and Podgursky 2000). An unexpectedly high proportion of mid-career applicants is now successfully entering teaching, with many coming through alternative routes; 47% in California, 46% in Massachusetts, 32% in Florida and 28% in Michigan (Johnson, Birkeland and Peske 2004). Some states such as Massachusetts, Missouri and Texas specifically authorise programmes that recruit applicants who are willing to work in high-poverty or low-achieving schools (Blair 2003).…”
Section: Initiatives To Attract Under-represented Groups To Higher Edmentioning
confidence: 95%
“…Existing research highlights that while many of these teachers find the programs satisfactory, they desired more preparation in content-based pedagogy and higher quality student-teaching placements (in programs where student teaching is offered). In addition, states are challenged with how to ensure quality of participants in these programs (Johnson, Birkland, & Peske, 2005), and recent research suggests that contentbased pedagogy is a critical factor contributing to teacher retention (Ingersoll, Merrill, & May, 2014). If alternative pathway programs become incentivized at a national level, we must be prepared to challenge their negative impact using research on teacher preparation, teacher quality, and student learning.…”
Section: The Perpetuation Of Free Market Ideology: the Increase In Almentioning
confidence: 99%